Introduction to practice of molecular simulation : molecular dynamics, Monte Carlo, Brownian dynamics, Lattice Boltzmann, dissipative particle dynamics - Satoh, Akira (Elsevier insights., 2011)
This book presents the most important and main concepts of the molecular and microsimulation techniques. Itenables readers to improve their skills for developing simulation programs by providing physical problems and sample simulation programs for them to use. Provides tools to develop skills in developing simulations programsIncludes sample simulation programs for the reader to useAppendix explains Fortran and C languages in simple terms to allow the non-expert to use them.